The Faraday filter-based spectrometer: an instrument to study sodium nightglow and associated sodium and oxygen chemistry in the mesopause region - Harrell, Sean David, author; She, Chiao-Yao, advisor; Krueger, David A., advisor; Roberts, Jacob Lyman, committee member; Reising, Steven C., committee member (Colorado State University. Libraries, 2010)
The newly developed Faraday Filter-Based Spectrometer (FFBS) makes possible spectroscopic study of the sodium nightglow in the mesopause region (80-110 km) of the atmosphere. This dissertation details the theory, design, and initial results of this instrument. The ratio of various combinations of NaD2 and NaD1 emission intensities can provide information on the oxygen and sodium chemistry in the mesosphere and lower thermosphere (MLT) region. Early understanding of the production of sodium nightglow utilized the series of chemical reactions known as the Chapman Mechanism. This mechanism involves both sodium and various oxygen species to produce excited states of sodium, which then relax to the ground state and emit light. The emitted light is centered at two wavelengths: D2 (589.158 nm) and D1 (589.756 nm). If the excited states are populated according to the statistical weights of their spin-orbit coupling the RD= D2/D1 intensity ratio should be 2; however there is no a priori reason that the spin-orbit states should be populated statistically in the Chapman mechanism. While early measurement of RD yields a value of 1.98±0.1, more recent measurements show a variation from 1.3 to 1.8; it peaks at the equinoxes and reaches minimum at the solstices. A possible explanation for this variation utilizes a modification to the Chapman Mechanism, which relates the RD value to variations in the atomic oxygen to molecular oxygen, [O]/[O2], concentration ratio through two different chemical pathways for sodium nightglow production. The FFBS is designed to measure RD, the fractional contribution of the two chemical pathways of the modified Chapman Mechanism, and other parameters which are directly proportional to [O]/[O2]. These parameters will help to test the validity of the modified Chapman mechanism. The delineation of the two chemical pathways requires an instrument with a spectral resolution of 0.0002 nm, something that is not possible with traditional spectroscopic instruments. The solution presented here utilizes two ultra narrowband sodium vapor Faraday filters. These utilize the Faraday rotation of light due to the Zeeman splitting of energy levels of sodium atoms in a vapor in an axial magnetic field between crossed polarizers to create an optical filter near both the D1 and D2 resonances with a full width, half maximum bandwidth of approximately 4 GHz (0.004 nm). This leads to a resolution that is good enough to distinguish the two different sodium nightglow spectral linewidths produced by the two pathways of the modified Chapman Mechanism which differ by 1.7 GHz. As a result, the FFBS is able to determine the fractional contribution from each pathway, as well as RD. Therefore the FFBS provides a new method of investigating [O]/[O2] in the mesopause region remotely from the ground. Data from this instrument supports the previous conclusion of a varying RD, with 2009 autumnal equinox measurements averaging around 1.68 and 2010 vernal equinox measurements averaging around 1.52, qualitatively in agreement with previous results by Slanger et al. (2005). In addition to RD, the first known measurements of parameters specific to the modified Chapman mechanism are presented and discussed. The dissertation concludes with a discussion of future work needed to convert the FFBS measurements into [O]/[O2] values, as well as future plans for the FFBS instrument.
Keywords: sodium nightglow; mesosphere lower thermosphere; sodium chemistry; oxygen chemistry; Atmospheric temperature -- Measurement; Airglow; Mesospheric thermodynamics; Spectrometer